Emotional Expressions as Speech Act Analogs. Issue 5 (December 2018) - Scarantino, Andrea
Abstract: In this article I articulate the Theory of Affective Pragmatics, which combines insights from the Basic Emotion View and the Behavioral Ecology View of emotional expressions. My core thesis is that emotional expressions are ways of manifesting one's emotions but also of representing states of affairs, directing other people's behaviors, and committing to future courses of actions. Since these are some of the main things we can do with language, my article's take home message is that, from a communicative point of view, much of what we can do with language we can also do with nonverbal emotional expressions.